Prevalence and Etiological Factors of Dental Trauma among 12- and 15-Year-Old Schoolchildren of Lebanon: A National Study - Chirine Abdel Malak; Carole Chakar; Alain Romanos; Samar Rachidi (The Scientific World Journal)
Background. Traumatic dental injuries represent nearly 5% of children and adolescents’ injuries leading to serious medical and psychological issues. This current study aims to evaluate the prevalence of dental trauma and its potential association with different predisposing factors among 12-and 15-year-old schoolchildren in Lebanon. Materials and Methods. 7902 schoolchildren, 3806 male and 4096 female aged 12 years (n = 3985) and 15 years (n = 3917), were recruited by a stratified multistaged randomized cluster sampling method from public and private schools and were clinically examined in a national cross-sectional study. WHO criteria were used to assess anterior permanent teeth; the nature of trauma, the tooth involved, the size of the incisal overjet, and the type of the lip coverage were furthermore assessed. Data regarding age, sex, and causes of TDI were recorded through a structured questionnaire. Results. The prevalence of dental trauma to anterior teeth was 10.9%. Maxillary central incisors (83.7%) were commonly affected. The most common type of injury was enamel fracture (68.3%), falls being the main reason (52.5%). Increased overjet (OR = 2.32, p = 0.034), deficient lip coverage (OR = 5.73, p = 0.019), and gender (OR = 5.36, p ≤ 0.001) were significant predisposing factors for dental trauma. Conclusion. This research highlighted many predisposing factors for dental trauma that affect commonly the anterior teeth. Based on these results, the implementation of strategic preventive measurements targeting especially the identified risk groups remains crucial.